The perfectionist's guide to losing control a path to peace and power - Schafler, Katherine Morgan (New York Penguin, 2023)
From psychotherapist Katherine Morgan Schafler, an invitation to every "recovering perfectionist" to challenge the way they look at perfectionism, and the way they look at themselves. We've been looking at perfectionism all wrong. As psychotherapist and former on-site therapist at Google Katherine Morgan Schafler argues in The Perfectionist's Guide to Losing Control, you don't have to stop being a perfectionist to be healthy. For women who are sick of being given the generic advice to "find balance," a new approach has arrived. Which of the five types of perfectionist are you? Classic, intense, Parisian, messy, or procrastinator? As you identify your unique perfectionist profile, you'll learn how to manage each form of perfectionism to work for you, not against you. Beyond managing it, you'll learn how to embrace and even enjoy your perfectionism. Yes, enjoy! Full of stories and brimming with humor, empathy, and depth, this book is a love letter to the ambitious, high achieving, full-of-life clients who filled the author's private practice, and who changed her life. It's a clarion call for all women to dare to want more without feeling greedy or ungrateful. Ultimately, this book will show you how to make the single greatest trade you'll ever make in your life, which is to exchange superficial control for real power"
Includes bibliographical references (pages 304-314) and index.
Keywords: Perfectionism (Personality trait)